Reduced myofibrillar connectivity and increased Z-disk width in nebulin-deficient skeletal muscle - Tonino, Paola; Pappas, Christopher T.; Hudson, Bryan D.; Labeit, Siegfried; Gregorio, Carol C.; Granzier, Henk (Journal of cell science, 2010)
A prominent feature of striated muscle is the regular lateral alignment of adjacent sarcomeres. An important intermyofibrillar linking protein is the intermediate filament protein desmin, and based on biochemical and structural studies in primary cultures of myocytes it has been proposed that desmin interacts with the sarcomeric protein nebulin. Here we tested whether nebulin is part of a novel biomechanical linker complex, by using a recently developed nebulin knockout (KO) mouse model and measuring Z-disk displacement in adjacent myofibrils of both extensor digitorum longus (EDL) and soleus muscle. Z-disk displacement increased as sarcomere length (SL) was increased and the increase was significantly larger in KO fibers than in wild-type (WT) fibers; results in 3-day-old and 10-day-old mice were similar. Immunoelectron microscopy revealed reduced levels of desmin in intermyofibrillar spaces adjacent to Z-disks in KO fibers compared with WT fibers. We also performed siRNA knockdown of nebulin and expressed modules within the Z-disk portion of nebulin (M160-M170) in quail myotubes and found that this prevented the mature Z-disk localization of desmin filaments. Combined, these data suggest a model in which desmin attaches to the Z-disk through an interaction with nebulin. Finally, because nebulin has been proposed to play a role in specifying Z-disk width, we also measured Z-disk width in nebulin KO mice. Results show that most Z-disks of KO mice were modestly increased in width (~80 nm in soleus and ~40 nm in EDL fibers) whereas a small subset had severely increased widths (up to ~1 μm) and resembled nemaline rod bodies. In summary, structural studies on a nebulin KO mouse show that in the absence of nebulin, Z-disks are significantly wider and that myofibrils are misaligned. Thus the functional roles of nebulin extend beyond thin filament length regulation and include roles in maintaining physiological Z-disk widths and myofibrillar connectivity.
Gesehen am 28.11.2023